PENGUJIAN EFEKTIFITAS DAYA TANGKAP JENIS PERANGKAP WALANG SANGIT (Leptocorisa oratorius) PADA TANAMAN PADI SAWAH - Damaskus Angki; Ni Putu Pandawani; I Made Sukerta (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
This research is entitled Testing the Effectiveness of Catching Types of Trap Walang Sangit (Leptocorisa oratorius) in Rice Fields. Walang sangit (Leptocorisa oratorius) is an important pest that attacks rice commodities. Walang sangit attacks when the rice enters the generative phase (ripe milk) by sucking the liquid on the rice grains, causing the rice grains to become empty. Environmentally friendly control that can be used is to use traps. This study aims to determine the trapping capacity of this type of trap against the pest in rice plants. The study was conducted using a Two-Treatment Paired Experimental Design. The study consisted of two treatments, namely the lamp trap (LT) and the carcass trap (CT). Observations were made eighteen (18) times as a replication. Lamp traps and crab carcass traps provide different catching power on the number of insect pests of walang sangit in rice plants. Crab carcass traps during the study showed that the catch power of carrion bugs was 127.85% higher than that of light traps. Insect pests found in the research rice fields were legged ladybug (Anasa tristis), green ladybug (Nezara viridula), grasshopper (Dissosteira carolina), beetle (Oulena melanoplus).